Capital humano e estrutura de capital: evidência de empresas brasileiras - Choi, Duk Young (2011)
This study verified jointly the determinants of capital structure and the effect of human capital cost on employee payment in Brazilian companies, based on the model of Berk, Stanton and Zechner (2010). As results, we could infer that the employee payment increases 0.26% for each percent of increase in leverage. Moreover, it is possible to observe that more capitalintensive company pays higher wage and the individual characteristics of CEO can define leverage level of the firm. Additionally, this study also confirms empirically the validity of some theories about capital structu re, like pecking order theory, substitution between debt and dividends, and negative correlation between risk and leverage.